DEVELOPING LIBRARIKA BASED DIGITAL LIBRARY TO EASE EFL STUDENT ACCESS TO LEARNING RESOURCES DURING THE COVID-19 PANDEMIC - Rosmania Rima; Rahman Hakim (Lembaga Penelitian (The Institute of Research) Universitas Swadaya Gunung Jati, 2022)
This study aims at developing a digital library that makes it easier for students majoring in English Education to access learning resources. This study adapts 7 of the 10 steps of the Research and Development (R&D) design by Borg and Gall (1983). The steps involve research and information gathering, planning, developing the initial product, preliminary field testing, major product revisions, main field testing and revision of operational products. Data are collected using questionnaires, observation and expert validation. The study shows (1 )the feasibility of digital library products as validated by the experts is in the average score of 3.54 criteria which indicates very good; (2) the registration, cataloguing, charging and discharging tasks are achieved within average time spent 207 seconds, 192 second and 34 seconds signifying the simplicity and efficiency of the template. (3) the users’ response on the attractiveness and convenience use of digital libraries shows that 85.39% respondents state that the product is very interesting and easy for use. Conclusions from the results of validation, trials and responses prove that the Librarika-Based digital library is feasible to use and can assist students in supporting lectures, ease the access to catalogues of library collections available at the English Department library and for sure avoid direct physical contact between members and librarian during the Covid-19 pandemic.